Polemik Kehamilan sebagai Alasan Mendesak Poligami: Kajian Gender dan Kepatutan Hukum dalam Putusan Nomor.2903/PDT.G/2022/PA.MJL - Putri Ainil Yakin; Riyan Ramdhani; Siti Nur Fatoni (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study examines the issue of premarital pregnancy being used as an urgent justification for polygamy in the Majalengka Religious Court Decision Number 2903/Pdt.G/2022/PA.Mjl. The research employs a normative juridical method with a case approach to assess whether the judges’ considerations align with the Marriage Law, Government Regulation No. 9 of 1975, the Compilation of Islamic Law, and principles of gender justice. The findings indicate that the judges granted the polygamy request based on the fulfillment of administrative requirements, the economic capability of the applicant, and the consent of the first wife. The pregnancy of the prospective second wife was treated as a factual urgent condition used to legitimize the marriage through polygamy. However, from a gender perspective, relying on a non-marital pregnancy as a justification for polygamy may overlook women’s protection and reinforce unequal power relations. The judges’ considerations emphasized procedural compliance rather than a substantive evaluation of legal propriety, fairness, and the social implications for women. This study highlights the need for integrating gender-sensitive perspectives and stricter standards of legal propriety to prevent the misuse of pregnancy as a basis for authorizing polygamy.